Hubungan Power Otot Tungkai dan Koordinasi Mata Tangan terhadap Keterampilan Smash pada Permainan Bola Voly Ekstrakulikuler Penjas Universitas DEHASEN Bengkulu - Novri Rajaski (Silampari Jurnal Olahraga, 2021)
The background of this study is volleyball extracurricular athletes do not yet have good skills and accuracy in doing smash. This study aims to determine the correlation between leg muscle strength and hand-eye coordination with smash skills in extracurricular volleyball games at the University of Dehasen Bengkulu. This study uses a survey method and correlational research type with Product moment statistics, this study uses samples of 15 athletes who were taken by purposive sampling technique. Based on the significance test of the correlation between leg muscle strength (X1) and hand-eye coordination (X2) on smash skills (Y) as has been obtained F count = 1.491> Ftable = 3.89 at a significant level = 0.05. It can be concluded that there is a correlation between leg muscle strength (X1) and hand-eye coordination (X2) on smash skills (Y) in the extracurricular volleyball game of Physical Education, in the University of Dehasen Bengkulu